IMPACT OF SERVICE QUALITY, ATMOSPHERE OF STORE, PRICE AND WORD OF MOUTH ON PURCHASE DECISIONS IN SWIWINGS, JEMBER - Rendra Pradana Perkasa; Muhammad Firdaus; Amien Pudjanarso (STIE Mandala Jember, 2021)
Culinary business in JemberRegency is increasing and developing rapidly. This phenomenon causes the consumer's various culinary choices. With the existing of competition in culinary business, triggers the employers to move faster in attracting consumers. Swiwings Jember has to be able to take advantage of business opportunity and try hard to apply marketing strategy and factors that can impact the purchasing. This research aims to determine the influence of Service quality, Store atmosphere, Price and Word of Mouth toward the buyingdecision in Swiwings Jember. This type of reseacrh is quantitative reseacrh. The technique uses purposive sampling technique. The research sample used was 50 respondents.This study used tools of analysis such as: Instrument test, Classic Assumption test, and Multiple Linear Regression Analysis. Hyphotesis is done using the t and F test. It is know that using the t test of Service Quality, Store Atmospheric and Price does not have a partially significant effect on the Purchasing Decision, whereas Word of Mouth has a partially significant effect on the Purchasing Decision. It is know that using the F test Service Quality, Store Atmosphere, Price and Word of Mouth have the significant simultaneous effect in purchasing decision. Keywords:Service Quality, Store’s Atmosphere, Price, Word of Mouth and Purchasing Decisions